2012
DOI: 10.1371/journal.pone.0032012
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cold-Regulated Cold Shock Domain Containing Protein from Scallop Chlamys farreri with Nucleic Acid-Binding Activity

Abstract: BackgroundThe cold shock domain (CSD) containing proteins (CSDPs) are one group of the evolutionarily conserved nucleic acid-binding proteins widely distributed in bacteria, plants, animals, and involved in various cellular processes, including adaptation to low temperature, cellular growth, nutrient stress and stationary phase.MethodologyThe cDNA of a novel CSDP was cloned from Zhikong scallop Chlamys farreri (designated as CfCSP) by expressed sequence tag (EST) analysis and rapid amplification of cDNA ends (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…To prevent freezing during winter, E. pela must undergo extensive dehydration and must clear ice nuclei substances from the gut and hemolymph (Carrasco et al ., ). Cold adaptation proteins have also been implicated in tolerance to low temperatures (De Leeuw et al ., ; Yang et al ., ). In the present study, these genes were identified in the transcriptome but were absent in the proteome.…”
Section: Discussionmentioning
confidence: 97%
“…To prevent freezing during winter, E. pela must undergo extensive dehydration and must clear ice nuclei substances from the gut and hemolymph (Carrasco et al ., ). Cold adaptation proteins have also been implicated in tolerance to low temperatures (De Leeuw et al ., ; Yang et al ., ). In the present study, these genes were identified in the transcriptome but were absent in the proteome.…”
Section: Discussionmentioning
confidence: 97%
“…Two nucleic acid binding proteins (NABP1, spots 15, R35) showed altered abundance in both the shoots and roots under salt stress. NABP is a small and highly conserved protein with nucleic acid chaperone activity that binds single-stranded nucleic acids [ 69 ]. One group of NABPs is the cold shock domain (CSD) containing proteins, and these CSDPs are involved in various cellular processes, including adaptation to low temperatures, cellular growth, nutrient stress, and the stationary phase [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SYBR Green RT-PCR assay was carried out and analyzed as previously described [23] . The comparative average cycle threshold method was used to analyze the mRNA expression level of AiHSP70, and the value stood for an n-fold difference relative to the calibrator [24] .…”
Section: Methodsmentioning
confidence: 99%